Electrical properties of n-SnS₂/n-CdIn₂Te₄ heterostructure - Gorley, P.M.; Grushka, Z.M.; Grushka, O.G.; Gorley, P.P.; Zabolotsky, I.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Using the method of deposition over the optical contact, the authors created nSnS2/n-CdIn₂Te₄ heterojunction and investigated temperature evolution of its currentvoltage characteristics under the forward bias U ≤ 3 V. Analyzing temperature dependence of the curves obtained, the main mechanisms of current transport through the semiconductor contact were determined, allowing prediction of successful possible applications of the heterojunction studied under high temperatures and elevated radiation due to the parameters of the base semiconductors and the diode structure itself.